2003
DOI: 10.1021/jm0209937
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening for Submicromolar Leads of tRNA-guanine Transglycosylase Based on a New Unexpected Binding Mode Detected by Crystal Structure Analysis

Abstract: Eubacterial tRNA-guanine transglycosylase (TGT) is involved in the hypermodification of cognate tRNAs, leading to the exchange of G34 by preQ1 at the wobble position in the anticodon loop. Mutation of the tgt gene in Shigella flexneri results in a significant loss of pathogenicity of the bacterium due to inefficient translation of a virulence protein mRNA. Herein, we describe the discovery of a ligand with an unexpected binding mode. On the basis of this binding mode, three slightly deviating pharmacophore hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
101
2
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 43 publications
1
101
2
3
Order By: Relevance
“…Numerous successful applications of this strategy have been reported in the literature. [15][16][17][18][19] In this study, we have shown that different virtual-screening methods generally seem to provide complementary hit lists of actives. Moreover, it is known that ligand-based virtual screenings based on different reference ligands or docking into different protein structures [46] provide different sets of actives.…”
Section: Application Of Virtual-screening Hypotheses Derived From Mulmentioning
confidence: 89%
“…Numerous successful applications of this strategy have been reported in the literature. [15][16][17][18][19] In this study, we have shown that different virtual-screening methods generally seem to provide complementary hit lists of actives. Moreover, it is known that ligand-based virtual screenings based on different reference ligands or docking into different protein structures [46] provide different sets of actives.…”
Section: Application Of Virtual-screening Hypotheses Derived From Mulmentioning
confidence: 89%
“…Docking screens compound libraries for molecules that physically complement protein-binding sites. The technique has been used to discover new ligands in the ''lead-like'' (typically Յ350 Da) or drug-like ranges (typically Յ500 Da) (12,13); some of these new ligands have been determined in complex with their targets by crystallography in geometries consistent with the docking predictions (14)(15)(16)(17). Docking has also been used to prioritize molecules for fragment-based screens for several targets (5,(18)(19)(20).…”
mentioning
confidence: 99%
“…Recently, the tgt gene has been implicated in the virulence of Shigella flexneri, a dysentery-causing bacterium (9,10). Given this, TGT presents itself as a potential novel antibiotic target (11,12).…”
mentioning
confidence: 99%